The Influence of Esports on Adolescents' Social Skills - Mulyadi, Djakwan Vici; Fitri, Mustika; Williyanto, Septian (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2023)
The incredible popularity of video games among teenagers today is a direct result of technological advances over the last few decades. With smartphones that are now more and more available to the general public. Previous research findings are still raising concerns in the esports community about how teenage esports players can provide valuable socializing time with peers and family. and esports players show that interacting with friends online is more enjoyable and satisfying than doing it in person. The study aims to test the impact of esports on adolescent social skills. This research is quantitative and correlational. The respondents in this study were teenagers who often played esports games, which amounted to 13 respondents. Selection of research subjects using purposive sampling method. This study uses the Real and Electronic Communication Skills questionnaire (RECS). The data gathered showed that five teenagers had low social skills, four people with adequate social skill, three people with high social skills and one person with very high social skill.